Body Shaming dan Self-Confidence pada Remaja Karang Taruna di Kampung Tengah, Kecamatan Pinggir, Kabupaten Bengkalis - Alvina Damayani; Muhammad Jais; Viony Syafitra (Program Studi Pendidikan Masyarakat, 2026)
Abstract: Body shaming refers to comments, judgments, or treatment that demean individuals based on physical appearance and may be associated with the development of adolescents’ self-confidence. This study aimed to describe the levels of body shaming and self-confidence and to examine the predictive contribution of body shaming to self-confidence among youth organization members in Kampung Tengah, Pinggir District, Bengkalis Regency. A quantitative ex-post facto design was employed. The population consisted of 110 adolescents, and 87 respondents were selected using the Slovin formula at a 5% margin of error and simple random sampling. Data were collected using five-point Likert questionnaires. The self-confidence instrument comprised 40 valid items with a Cronbach’s alpha of 0.954, while the body-shaming instrument comprised 39 valid items with a reliability coefficient of 0.963. Descriptive statistics, normality and linearity tests, Pearson correlation, and simple linear regression were applied. Body shaming was classified as moderately high (M=3.69), whereas self-confidence was moderate (M=3.39). The variables were positively and significantly correlated (r=0.512; p<0.001). Regression analysis produced B=0.503 (t=5.499; p<0.001) and R²=0.262, indicating that body shaming explained 26.2% of the variance in self-confidence. This positive direction contradicts the theoretical expectation and indicates that the coding of positively and negatively worded items should be verified before substantive inference. Youth organizations should promote anti-body-shaming education, inclusive communication, and positive body-image development. Abstrak: Body shaming merupakan komentar, penilaian, atau perlakuan yang merendahkan individu berdasarkan penampilan fisik dan berpotensi berkaitan dengan pembentukan kepercayaan diri remaja. Penelitian ini bertujuan mendeskripsikan tingkat body shaming dan self-confidence serta menganalisis kontribusi prediktif body shaming terhadap self-confidence pada remaja Karang Taruna di Kampung Tengah, Kecamatan Pinggir, Kabupaten Bengkalis. Penelitian menggunakan pendekatan kuantitatif dengan desain ex-post facto. Populasi berjumlah 110 remaja dan sampel sebanyak 87 responden ditentukan menggunakan rumus Slovin pada tingkat kesalahan 5% serta dipilih dengan simple random sampling. Data dikumpulkan menggunakan kuesioner skala Likert lima tingkat. Instrumen self-confidence terdiri atas 40 item valid dengan reliabilitas Cronbach’s alpha 0,954, sedangkan instrumen body shaming terdiri atas 39 item valid dengan reliabilitas 0,963. Analisis meliputi statistik deskriptif, uji normalitas, uji linearitas, korelasi Pearson, dan regresi linear sederhana. Hasil menunjukkan bahwa body shaming berada pada kategori cukup tinggi (M=3,69), sedangkan self-confidence berada pada kategori sedang (M=3,39). Kedua variabel berkorelasi positif dan signifikan (r=0,512; p<0,001). Regresi menghasilkan koefisien B=0,503 (t=5,499; p<0,001) dan R²=0,262, sehingga body shaming menjelaskan 26,2% variasi self-confidence. Arah positif ini tidak sejalan dengan ekspektasi teoritis dan mengindikasikan perlunya verifikasi pengodean item positif-negatif sebelum inferensi substantif dibuat. Secara praktis, Karang Taruna perlu mengembangkan edukasi anti-body shaming, komunikasi inklusif, dan penguatan citra diri positif.